(untitled) (Conference Zone, 2021)
Is there a blessing more precious in this world than the peace and tranquility of the motherland?! More courageous than to protect him? The military is literally the epitome of such courage and fortitude. This profession requires true patriotism, dedication, and strong will. The military is the guarantee of our peaceful, medicated, prosperous life today. As long as they exist, our country is peaceful, the sky is clear and our borders are strong. That is why the military is called the profession of the brave, and the defenders of the Motherland are always glorified and honored. This article discusses the responsibilities of being in the military and the opportunities offered to honorable professionals.